PERBANDINGAN PENGARUH LATIHAN ANTARA PASSING BAWAH BERPASANGAN DENGAN PASSING BAWAH PERORANGAN TERHADAP KETERAMPILAN PASSING BAWAH PADA TIM BOLA VOLI PUTRA MAN 1 PEKANBARU - Anjellina Jasni; Zainur Zainur; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the comparison of the effect of trainingbetween paired under-passing and individual under-passing on the under-passing skillsof the men's volleyball team at MAN 1 Pekanbaru. This research was conducted atMAN 1 Pekanbaru, Jl. Milkfish No. 51 A, Tangkerang Tengah, Marpoyan Damai, Julyto December 2019. The population which is also the sample in this study amounted to12 students of the men's volleyball team MAN 1 Pekanbaru. From the research results,it was found that there was an effect of paired under-passing training on the underpassingskills of the Men's Volleyball Team MAN 1 Pekanbaru as evidenced by tcount12.15> ttable 2.015 at α = 0.05. There is an effect of individual under-passing trainingon the under-passing skills of the men's volleyball team MAN 1 Pekanbaru as evidencedby Tcount 9.42> Ttable 2.015 at α = 0.05. There is a significant comparison betweenpaired under-passing practice and individual under-passing practice on the underpassingskills of the Men's Volleyball Team MAN 1 Pekanbaru. Where the effect ofpaired under passing practice is better when compared to individual under-passingtraining on the under-passing skills of the Men's Volleyball Team MAN 1 Pekanbaru.Key Words: Comparison of Exercise Effect, Lower Passing, Passing Skills